Windows 7 sp1 : - Matthews, Marty (McGraw-Hill, 2011)
Get up to speed with Windows 7 right away--the QuickSteps way. Fully updated to cover Windows 7 SP1, Windows Live Mail 2011, and Internet Explorer 9, this book includes color screenshots and clear explanations that show you how to maximize the powerful features and upgrades available in Windows 7. Find out how to navigate and customize your desktop, store data, manage files, connect to the Internet, use email, add hardware and software, work with photos, and enjoy multimedia. Managing security and setting up a wired or wireless network are also covered. Start using Windows 7 in no time with help from this hands-on guide.